Maximum bite force in relation to maximum mouth opening among primary school children - Athraa H Medhat; Aseel H Al Haidar (College of Dentistry/ University of Baghdad, 2019)
Background: The vertical distance between the upper and lower incisal edge of the central incisors when the mouth is opened as wide as possible is called maximum mouth opening (MMO). Any pathological change in the masticatory system had a direct effect on the maximal mouth opening. The aim of this study was to evaluate the relationship between the maximum bite force and the maximum mouth opening among group of children. Materials and methods: Four hundred children of both genders were included in this study, their age ranged from eight to ten years. Anterior and posterior (right, left) bite force were measured using bite force sensor. Maximum mouth opening was evaluated by electronic digital caliper. Data was statistically analyzed by descriptive statistics and by using paired t‑test and Chi‑square test. Results: The value of Maximum mouth opening was increased with the increasing of age in both genders; however, boys had higher value of Maximum Mouth opening than that of girls. A significant difference was found between genders among 9 years old children concerning the maximum bite force. A weak positive relation was observed between Maximum mouth opening and Maximum Bite Force among the boys in both of the age groups. Conclusions: In this study, a significant positive correlation was found between Maximum bite force and Maximum Mouth opening for boys, as they had higher mean value of maximum mouth opening and maximum bite force than girls.